Peran Kegiatan Pesta Siaga dalam Penanaman Karakter pada Siswa Sekolah Dasar - Qorneila, Yutika; Nurharini, Atip; Rachmawati S, Aulia Intan; Andika, Fadhlu Dwi; Kholifah, Laela Musri (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Character cultivation is one thing that must be implemented from an early age. Apart from being done in the home environment, character cultivation can also be done in the school environment. One way to instill character in children in the school environment is by participating in extracurricular programs at school. One of the extracurriculars that is mandatory in elementary school is scouting. In scouting there is an activity that can instill character in children from an early age, namely the Alert Party. The Alert Party is a series of scout agendas or activities which are attended by students aged 7-10 years. Having this alert party can certainly help in cultivating the character of elementary school students. In this research, the author will analyze in more depth the role of alert party activities in cultivating character in elementary school students. The method used by the author is a descriptive qualitative method. The author uses data collection techniques in the form of interviews, observation and documentation. The results of this research show that alert parties have a role in cultivating the character of elementary school students. Characters that can be taken from this alert party activity include discipline and responsibility.